Inhibition of Vascular c‐Jun N‐Terminal Kinase 2 Improves Obesity‐Induced Endothelial Dysfunction After Roux‐en‐Y Gastric Bypass. Issue 11 (14th November 2017) - Doytcheva, Petia; Bächler, Thomas; Tarasco, Erika; Marzolla, Vincenzo; Engeli, Michael; Pellegrini, Giovanni; Stivala, Simona; Rohrer, Lucia; Tona, Francesco; Camici, Giovanni G.; Vanhoutte, Paul M.; Matter, Christian M.; et al.
Abstract : Background: Roux‐en‐Y gastric bypass (RYGB) reduces obesity‐associated comorbidities and cardiovascular mortality. RYGB improves endothelial dysfunction, reducing c‐Jun N‐terminal kinase (JNK) vascular phosphorylation. JNK activation links obesity with insulin resistance and endothelial dysfunction. Herein, we examined whether JNK1 or JNK2 mediates obesity‐induced endothelial dysfunction and if pharmacological JNK inhibition can mimic RYGB vascular benefits. Methods and Results: After 7 weeks of a high‐fat high‐cholesterol diet, obese rats underwent RYGB or sham surgery; sham–operated ad libitum–fed rats received, for 8 days, either the control peptide D‐TAT or the JNK peptide inhibitor D‐JNKi‐1 (20 mg/kg per day subcutaneous). JNK peptide inhibitor D‐JNKi‐1 treatment improved endothelial vasorelaxation in response to insulin and glucagon‐like peptide‐1, as observed after RYGB. Obesity increased aortic phosphorylation of JNK2, but not of JNK1. RYGB and JNK peptide inhibitor D‐JNKi‐1 treatment blunted aortic JNK2 phosphorylation via activation of glucagon‐like peptide‐1–mediated signaling. The inhibitory phosphorylation of insulin receptor substrate‐1 was reduced, whereas the protein kinase B/endothelial NO synthase pathway was increased and oxidative stress was decreased, resulting in improved vascular NO bioavailability. Conclusions: Decreased aortic JNK2 phosphorylation after RYGB rapidly improves obesity‐induced endothelial dysfunction. Pharmacological JNK inhibition mimics the endothelial protective effects of RYGB. These findings highlight the therapeutic potential of novel strategies targeting vascular JNK2 against the severe cardiovascular disease associated with obesity.